PHYTOCHEMICAL SCREENING AND ANTIOXIDANT ACTIVITY TEST USING DPPH METHOD OF KLUWIH SEED (Artocarpus camansi Blanco) - Sulistiawati, Iqlimah; Saleh, Chairul; -, Erwin (JURNAL ATOMIK, 2021)
Phytochemical screening and antioxidant activity test using DPPH method of Kluwih seed (Artocarpus camansi Blanco) have been done. Maceration of Kluwih seed was carried out using methanol. The phytochemical test showed A. camansi contains secondary metabolites including alkaloids, phenolics, flavonoids and steroids. Based on the result of the antioxidant test using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method, the result exhibited that the crude extract had an IC50 value of 63.63 ppm.